Tissue-print and squash real-time PCR for direct detection of 'Candidatus Liberibacter' species in citrus plants and psyllid vectors - Bertolini, Edson; Felipe, R. T. A.; Sauer, A. V.; Lopes, S. A.; Arilla, A.; Vidal, Eduardo; Mourao Filho, F. A. A.; Nunes, W. M. C.; Bove, J. M.; López, María M.; Cambra, Mariano (2017)
Huanglongbing (HLB) disease is seriously threatening and/or damaging the citrus industry worldwide. Accurate detection of the three species associated with HLB disease, Candidatus Liberibacter asiaticus', Candidatus Liberibacter africanus' and CandidatusLiberibacter americanus', is essential for the preventive control of the disease. Real-time PCR is a useful tool for bacterial detection. However, nucleic acid purification steps limit the number of samples that can be processed by PCR. Universal detection of Ca.Liberibacter' species was achieved by direct tissue-printing and spotting of plant leaf petiole extracts or squashing of individual psyllids onto paper or nylon membranes. Primers were designed and used with TaqMan chemistry for accurate detection of the bacterium in immobilized targets (prints of 10 overlapping leaf pedicels per tree, or squashed single vectors), by extraction with water and direct use for real-time PCR. This simplified method was validated and could detect HLB-liberibacters in 100% of leaves with symptoms and 59% of symptomless leaves collected from HLB-infected trees. The use of direct assays as template showed good agreement with use of purified DNA (=076 +/- 0052). The squash assay allowed detection of the bacterium in 40% of mature Diaphorina citri that fed on leaves of HLB-infected trees with or without symptoms. A commercial ready-made kit based on this technology showed 96% accuracy in intra-laboratory performance studies. The simplified direct methods of sample preparation presented herein can be effectively adopted for use in rapid screening of HLB agents in extensive surveys, certification schemes or for epidemiological and research studies.